Assessing the UAVs' Requirements and Capabilities For Humanitarian Logistics Operations in Thailand - Natthajira Yeh; Chatchaya Siriwat; Nichapat Weeraburus; Waralee Rattanakijsuntorn (My University, 2023)
This article aims to identify and assess the design requirements and capabilities of unmanned aerial vehicles used in the area of humanitarian logistics, particularly for the delivery of aid packages, to alleviate the impact and casualties from natural disaster's victims in Thailand. Designed restrictions and sub-restrictions were identified from past literature and an expert interview. By applying a multi-criteria decision-making analysis tool, which is the analytical hierarchy process, design restrictions and sub-restrictions was quantified and prioritized. Primary data was collected through private, face-to-face interviews. Respondents are UAV pilots, UAV developers from associated industries, and UAV researcher. The computed outputs revealed that the payload capacity of the UAVs, the weight of aid packages, the flight range, and the battery power capacity were among the sub-restrictions with the highest relative importance, while flight performance is the most important restrictions in the drones' design requirements. On the contrary, the speed of UAV and the operating cost were the sub-restrictions with the smallest effect.
Keywords: Facility Location and Emergency Management; UAV Applications and Optimization; Vehicle Routing Optimization Methods